Evaluation of the test-retest repeatability of the Injury Severity Perception score in patients with acute whiplash-associated disorder - Robert Ferrari (Elsevier, 2015)
Objective: To determine the test-retest repeatability of the Injury Severity Perception (ISP) score in participants with acute whiplash-associated disorders (WADs). Methods: Consecutive patients with WAD, presenting in the acute stage to a primary care center, were asked to complete the ISP score. ISP was measured with a numerical rating scale that ranged from 0 to 10, on which subjects were asked to rate how severe (in terms of damage) they thought their injury was. The anchors were labeled ''no damage'' (0) and ''severe, and maybe permanent damage" (10). The ISP questionnaire was administered to the participants at the time of recruitment and again 7 days later. Repeatability was evaluated by calculating percentage agreement and Cohen kappa statistic between the two time points of measurement. Results: A total of 94 subjects (34 males, 60 females, mean age 40.6 ± 10.0 years, range 19-60 years) were included. The mean ISP score was 4.9 ± 1.7 (range 2-9 out of 10) at the time of recruitment and 5.1 ± 2.1 (range 2-9 out of 10) 7 days later. The percentage agreement between the two repeat measures of the ISP was 86% and the kappa coefficient was 0.79. Conclusion: This study suggests that the test-retest repeatability for the ISP is high and that it is thus likely to have a low risk of classification bias in prognostic studies. The ISP likely has adequate reliability for use in epidemiological research of WADs.